1970
DOI: 10.7589/0090-3558-6.4.211
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis in Imported Non-Human Primates

Abstract: In 1969, five cases of melioidosis in three separate outbreaks were diagnosed in nonhuman primates in the United States. In the first outbreak, two stump-tailed macaque monkeys (Macaca arctoides) developed signs of the disease approximately 6 months after purchase. A third animal, a chimpanzee (Pan troglodytes), probably acquired its infection from one of these monkeys. Two other unrelated cases involving a pig-tailed monkey (Macaca nemestrina) and a rhesus monkey (Macaca mulatta) were diagnosed. These monkeys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…The difference between the study reported here and that performed by Miller et al (28) is possibly a result of the route of infection, but it is also possibly a result of the strain of B. pseudomallei. However, reports of natural outbreaks in NHPs imported from areas of endemicity and recent studies in NHPs by Manzenuik et al (27) and Nelson et al (29) support the notion that NHPs are susceptible to infection with B. pseudomallei (1,14,20,27,29). Although historically conflicting data on the susceptibility of NHPs to melioidosis existed, it has become evident with the recent NHP studies and the models presented here that the NHP is a reasonable and valuable model system for studying melioidosis pathogenesis and for medical countermeasure evaluation.…”
Section: Discussionmentioning
confidence: 97%
“…The difference between the study reported here and that performed by Miller et al (28) is possibly a result of the route of infection, but it is also possibly a result of the strain of B. pseudomallei. However, reports of natural outbreaks in NHPs imported from areas of endemicity and recent studies in NHPs by Manzenuik et al (27) and Nelson et al (29) support the notion that NHPs are susceptible to infection with B. pseudomallei (1,14,20,27,29). Although historically conflicting data on the susceptibility of NHPs to melioidosis existed, it has become evident with the recent NHP studies and the models presented here that the NHP is a reasonable and valuable model system for studying melioidosis pathogenesis and for medical countermeasure evaluation.…”
Section: Discussionmentioning
confidence: 97%
“…Disease was recognized in these animals ranging from 3 days to 10 years after importation. 3,4,[13][14][15]19,21,26 The animal in this report had a stifle abscess at the time of arrival to our facility. Although Burkholderia was not definitively identified from this lesion, this may have been the initial site of infection, with progression to central nervous system and lung involvement 6 months later.…”
Section: Discussionmentioning
confidence: 99%
“…Longer incubations are often associated with subclinical infections, with fulminant disease developing during periods of host immunosuppression. 2,12,17,19,28 Clinical signs of melioidosis in all species are variable and depend on the route and dose of infection, virulence of the infecting bacterial strain, and perhaps most importantly, the immune status of the host and presence of concurrent chronic diseases. 6,11,12,28 The most common disease manifestations in people are pneumonia and septicemia with systemic abscess formation.…”
mentioning
confidence: 99%
“…Reports of naturally occurring melioidosis in NHPs have identified additional clinical features that are also prominent in human cases, including wasting, cough, nasal discharge, and a mild respiratory disease that can develop to an acute fulminant bronchopneumonia. 45,92 Similarly, an evaluation of IP and SC B. pseudomallei infection in Hamadryas baboons resulted in the same lung, liver, spleen, and lymph node tropisms observed in humans. 57 More recent efforts have been undertaken to evaluate the pathology of inhaled B. pseudomallei in the marmoset, rhesus macaque, and AGM.…”
Section: 17mentioning
confidence: 99%